(untitled) (Research, Society and Development, 2023)
Overweight is an important public health problem which needs an interdisciplinar treatment, mainly in adolescence, because of its complexity. Therefore, this study aimed to analyze the effects of interdisciplinary interventions on associated variables of the metabolic syndrome in overweight adolescentes. The age range selected to participate in the Study Group on Physical Education, Physiotherapy, Sports, Nutrition, and Performance was between 10 and 19 years who achieved the criteria. The adolescents received dietary and psychological guidance as well as instructions for physical exercise, for 12 weeks, and the data were collected before and after the intervention: waist circumference, blood pressure and laboratory tests (fasting blood glucose, triglycerides and lipid profile). Twenty-six adolescents completed the 12 weeks of intervention. After the intervention, a significantly reduced levels of glucose was showed (p = 0.004). Despite of non-statistically significant of the other variables were observed, it is possible to note that the average values of body weight, BMI, waist circumference, and triglycerides decreased after the intervention. Although, HDL cholesterol showed a slight increase. It is meaningful that 01 (3.86%) adolescent had overweight, 17 (65.38%) were obese and 8 (30.76%) were classified as severely obese. It was also observed that blood glucose levels showed a significant reduction after the intervention in all 3 groups, with the obese group showing the greatest decrease (p < 0.05). Thus, it was observed that interdisciplinary interventions positively impacted the indicators contributing to the development of metabolic syndrome.